Evaluation of exposure index (IgM) in orthopaedic radiography - Lança, Luís (2008)
The exposure index (lgM) obtained from a radiographic image may be a useful feedback indicator to the radiographer about the appropriate exposure level in routine clinical practice. This study aims to evaluate lgM in orthopaedic radiography performed in the standard clinical environment. We analysed the lgM of 267 exposures performed with an AGFA CR system. The mean value of lgM in our sample is 2.14. A significant difference (P=0.000<0.05) from 1.96 lgM reference is shown. Data show that 72% of exposures are above the 1.96 lgM and 42% are above the limit of 2.26. Median values of lgM are above 1.96 and below 2.26 for Speed class (SC) 200 (2.16) and SC400 (2.13). The interquartile range is lower in SC400 than in SC200. Data seem to indicate that lgM values are above the manufacturer’s reference of 1.96. Departmental exposure charts should be optimised to reduce the dose given to patients.